Addition of dextrose and caffeine to the intravenous treatment of milk fever in Holstein Friesian cattle - Ady Kurnianto; Novianto Meska Pratama (Ovozoa: Journal of Animal Reproduction, 2023)
A farmer reported a cow unable to stand 48 hours postpartum. The cow was a 2.5 years old dairy cow with a body weight of around 350 kg. The cow was fed elephant grass, standard concentrate (16–18%) crude protein, and drinking water ad libitum without mineral supplementation during the dry season. The cow's position and posture when lying down, ear temperature, and eye pupils were included in the physical examination. Availability of food and drink was examined to predict appetite and thirst. The results of the history and physical examination showed that the cow was unable to stand 48 hours after calving, had no appetite and eye reflexes, had cold ears, and trembling hind legs. The cow was laid on its right side, with its head turned to flank. Based on the anamnesis and physical examination, the cow was diagnosed as suffering from stage 2 puerperal hypocalcemia. The cow was infused via the jugular vein with a solution containing 270 mg calcium borogluconate, 70 mg magnesium borogluconate, 300 mg dextrose, 5 mg phosphorus element, 2 mg potassium chloride, and 5 mg caffeine per 1 mL of solution. Forty-five minutes after the infusion, the cow was able to stand, although it still looked weak. It could be concluded that the addition of dextrose and caffeine to the standard treatment of milk fever was beneficial for recovery.